Characterization of the complete chloroplast genome of Gymnocladus chinensis Baill - Xiao Feng; Zhao Yang; Wang Xiu-rong; Ya-yan Zhu (Mitochondrial DNA. Part B. Resources, 2021)
Gymnocladus chinensis Baill (Fam.: Leguminosae; Trib.: Caesalpinieae) are widely distributed in China. In this study, we assembled the complete chloroplast (cp) genome of G. chinensis. The total cp genome size was 165,315 bp in length, containing a large single-copy region of 92,356 bp, a small single-copy region of 20,449bp, and a pair of inverted repeat regions of 26,255 bp. The all GC content of G. chinensis cp was 34.95%. It encodes a total of 105 unique genes, including 75 protein-coding genes, 26 tRNA genes, and four rRNA genes. Seventeen genes contain a single intron, and two genes (ycf3 and clpP) have two introns. Phylogenetic analysis results strongly supported that G. chinensis was closely related to Angylocalyx braunii.